Asbabun Nuzul Surah Al-Mujadalah Ayat 11 Dalam Perspektif Pendidikan di Pesantren Modern Darul Ihsan - Maulidatul Husna; Dedi Masri; Muhammad Alfiansyah; Sri Wahyuni (Jurnal Bintang Pendidikan Indonesia, 2023)
This study aims to analyze thel asbabun nuzul of Q.S Al-mujadalah verse 11 which is rellated to the perspelctivel of education in the Modern Islamic Boarding School Darul Ihsan. Asbabun Nuzul surah Al-mujadalah versel 11 is about manners and morals when someone is in the assemby, so it is analyzed how the manners of the students or santri and santriwati in the Modern Islamic Boarding School Darul Ihsan when they are in the assemby. Asbabun Nulzul surah Al-mujadalah verse 11 is not only intended for students, but for all Muslims who are in an assemby of knowledge, both students and educators. such as the story when the Prophet opened an assemby and at that time the Badr came and no one gave him a seat, so the Prophet ordered other companions to gelt up and give a seat to the Badr who had just arrived, because whoever clears his seat during the assemby, Allah SWT will raise his degreel. This must be applied to students in all educational institutions and also in their daily lives, not spared from the students who study at boarding schools, adab and moras are the most important things that are seen and taught in pesantren, because in fact adab is higher than knowledge. So, for students who study in pesantren, it should bel emphasized to them about adab, especially when they are in the assemby of knowledge or in teaching and learning activities, adab used towards teachers, towards friends around and towards the boarding school environment.This research makes an important contribution in understanding the asbabun Nulzul of surah Al-mujadalah verse 11 in the perspective of education in the Modern Darul Ihsan Islamic Boarding School which is about adab when in the assemby, and the implication of this research is the importance and necessity of knowing how adab when in the assemby of knowledge for students.